2005
DOI: 10.1021/ic051471v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Preliminary Oxygenation Studies of Benzyl- and Ethyl-Substituted Pyridine Ligands of Carboxylate-Rich Diiron(II) Complexes

Abstract: In this study benzyl and ethyl groups were appended to pyridine and aniline ancillary ligands in diiron (II) complexes of the type [Fe 2 (μ-O 2 CAr R ) 2 (O 2 CAr R ) 2 (L) 2 ], where

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The oxygenation of methane by sMMO has been proposed to occur through various intermediates, such as compound P and compound Q, 4 in which the most labile intermediate compound Q has been supposed to contain two high-spin Fe IV ions based on Mössbauer spectroscopic study. 5 In model systems, although some diiron complexes, of which the ligands have consisted of carboxylate groups as an active site model in sMMO, [6][7][8][9][10][11][12][13] have been synthesized to understand the structure of compound Q, such a high valent Fe IV complex has not been obtained. (5-Et 3 tpa = tris(5-ethyl-2-pyridylmethyl)amine) with hydrogen peroxide in acetonitrile at À40 C. 14 The donor atom set of 5-Et 3 TPA the donor atoms are not carboxylate groups but N4 atoms set, and they have suggested that the structure of compound Q contains a Fe IV 2 (-O) 2 core.…”
Section: Introductionmentioning
confidence: 99%
“…The oxygenation of methane by sMMO has been proposed to occur through various intermediates, such as compound P and compound Q, 4 in which the most labile intermediate compound Q has been supposed to contain two high-spin Fe IV ions based on Mössbauer spectroscopic study. 5 In model systems, although some diiron complexes, of which the ligands have consisted of carboxylate groups as an active site model in sMMO, [6][7][8][9][10][11][12][13] have been synthesized to understand the structure of compound Q, such a high valent Fe IV complex has not been obtained. (5-Et 3 tpa = tris(5-ethyl-2-pyridylmethyl)amine) with hydrogen peroxide in acetonitrile at À40 C. 14 The donor atom set of 5-Et 3 TPA the donor atoms are not carboxylate groups but N4 atoms set, and they have suggested that the structure of compound Q contains a Fe IV 2 (-O) 2 core.…”
Section: Introductionmentioning
confidence: 99%
“…The phenyl linker was chosen to provide additional flexibility and to avoid a benzylic position that is readily oxidized, as previously established for these types of compounds. [22] Methoxy and hydroxy substituents were included to activate the phenyl ring toward electrophilic substitution, because hydroxylation of aromatic substrates occurs by electrophilic attack on the π -system, as observed for peroxo intermediates in sMMOH[7] and ToMOH. [50]…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent this problem, the substrates were tethered to ancillary neutral donor ligands. With the use of this approach, C–H activation of benzylic moieties in benzyl- and ethylpyridines,[22] oxidation of sulfides and phosphines,[23-25] and oxidative N -dealkylation reactions were achieved. [26-29] The extent of oxidation reflected the proximity of the substrate to the diiron center, and little or no oxidation was observed when a substrate moiety was installed in the meta or para position of the pyridine ligand.…”
Section: Introductionmentioning
confidence: 99%
“…This fortuitous discovery that high-valent diiron terphenylcarboxylate complexes could be intercepted by tethered substrates inspired subsequent studies of the reactivity of oxygenated intermediates toward organic moieties held in close proximity to the diiron center. Attachment of benzyl [84, 85], ethyl [85], ethynyl [86], phenoxyl [87], phosphido [84, 88], or sulfido [88, 89] units to an amine or pyridine ligand afforded a series of tethered substrates that could be easily incorporated into 13 , affording the corresponding diiron(II) compounds. After exposing the substrate/diiron(II) complex to O 2 , the reaction products were analyzed by gas chromatography-mass spectrometry (GC-MS).…”
Section: Ligand Platformsmentioning
confidence: 99%